Evolutionary Action Score of TP53 Analysis in Pathologically High-Risk Human Papillomavirus-Negative Head and Neck Cancer From a Phase 2 Clinical Trial: NRG Oncology Radiation Therapy Oncology Group 0234 - Chieko Michikawa, DDS, PhD; Pedro A. Torres-Saavedra, PhD; Natalie L. Silver, MD, MS; Paul M. Harari, MD; Merrill S. Kies, MD; David I. Rosenthal, MD; Quynh-Thu Le, MD; Richard C. Jordan, DDS, PhD; Dzifa Y. Duose, PhD; Saradhi Mallampati, DVM, PhD; Sanchit Trivedi, MS; Rajyalakshmi Luthra, PhD; et al. (Advances in Radiation Oncology, 2022)
Purpose: An evolutionary action scoring algorithm (EAp53) based on phylogenetic sequence variations stratifies patients with head and neck squamous cell carcinoma (HNSCC) bearing TP53 missense mutations as high-risk, associated with poor outcomes, or low-risk, with similar outcomes as TP53 wild-type, and has been validated as a reliable prognostic marker. We performed this study to further validate prior findings demonstrating that EAp53 is a prognostic marker for patients with locally advanced HNSCC and explored its predictive value for treatment outcomes to adjuvant bio-chemoradiotherapy. Methods and Materials: Eighty-one resection samples from patients treated surgically for stage III or IV human papillomavirus-negative HNSCC with high-risk pathologic features, who received either radiation therapy + cetuximab + cisplatin (cisplatin) or radiation therapy + cetuximab + docetaxel (docetaxel) as adjuvant treatment in a phase 2 study were subjected to TP53 targeted sequencing and EAp53 scoring to correlate with clinical outcomes. Due to the limited sample size, patients were combined into 2 EAp53 groups: (1) wild-type or low-risk; and (2) high-risk or other. Results: At a median follow-up of 9.8 years, there was a significant interaction between EAp53 group and treatment for overall survival (P = .008), disease-free survival (P = .05), and distant metastasis (DM; P = .004). In wild-type or low-risk group, the docetaxel arm showed significantly better overall survival (hazard ratio [HR] 0.11, [0.03-0.36]), disease-free survival (HR 0.24, [0.09-0.61]), and less DM (HR 0.04, [0.01-0.31]) than the cisplatin arm. In high-risk or other group, differences between treatments were not statistically significant. Conclusions: The docetaxel arm was associated with better survival than the cisplatin arm for patients with wild-type or low-risk EAp53. These benefits appear to be largely driven by a reduction in DM.